INTEGRATING HUMANISTIC IN READING MATERIAL FOR EIGHT GRADERS JUNIOR HIGH SCHOOL - Ritonga, Theresia Rosalina; Sulistyaningrum, Siti Drivoka (Journal of English Educational Study (JEES), 2025)
Education should aim at fostering human development and personal growth rather than focusing solely on higher test scores. Emphasizing these aspects will inherently boost intellectual achievements and better prepare students to contribute to both global and local societies. Human beings have an innate goodness and a natural tendency to learn, grow, and reach their full potential. Therefore, aligning education with these natural tendencies will make it more effective. This article investigates how integrating humanistic principles with students' reading abilities can enhance English language learning in the classroom. The research methods primarily utilize library materials, eliminating the need for fieldwork (Zed, 2008). The study's findings indicate that students can enhance their reading skills in a humanistic way, creating a classroom environment that aligns with the educational goal of fostering humanistic understanding of learning materials.